Mobile Right Atrial Thrombi in a Patient with the Hemoglobin SC Disease - H. O. Savage; N. Ding; O. Eso; B. Sachdev; D. L. Lefroy (Case Reports in Medicine)
The formation of Intracardiac thrombi is rare in the absence of structural heart disease or atrial fibrillation. We describe a case of spontaneous right atrial thrombus formation that occurred in a patient with a hypercoagulable condition who had been sub optimally anticoagulated.